2022
DOI: 10.3389/fvets.2022.881878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Porcine Clostridium perfringens on Intestinal Barrier, Immunity, and Quantitative Analysis of Intestinal Bacterial Communities in Mice

Abstract: Clostridium perfringens (C. perfringens) is one of the main pathogens which can cause a range of histotoxic and enteric diseases in humans or animals (pigs, or broilers). The Centers for Disease Control and Prevention (CDC) estimates these bacteria cause nearly 1 million illnesses in the United States every year. For animal husbandry, necrotizing enteritis caused by C. perfringens can cost the global livestock industry between $2 billion and $6 billion per year. C. perfringens-infected animals can be isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Our data indicated that C. perfringens infection shortened the colon length at 1 dpi ( Figure 2C ), suggesting potential colonic inflammation. Interestingly, mice infected with porcine C. perfringens displayed a shortened colon length in an infectious dose-dependent manner ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicated that C. perfringens infection shortened the colon length at 1 dpi ( Figure 2C ), suggesting potential colonic inflammation. Interestingly, mice infected with porcine C. perfringens displayed a shortened colon length in an infectious dose-dependent manner ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…As our previous study described, we used the Clostridium perfringens to construct a mouse model to test the effect of isolated strains in vivo [ 35 ]. We measured isolated strains’ function by analyzing the growth performance, immune status, and the population of beneficial and harmful bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…We exerted Nanodrop 2000 (Thermo Fisher Scientific Inc., Waltham, MA, USA) to quantify the purified insert-containing plasmids. Then target DNA copies were calculated [ 35 ]: …”
Section: Methodsmentioning
confidence: 99%
“…1 For animal husbandry, necrotizing enterocolitis linked with C. perfringens is responsible for an estimated economic loss between USD$2 and $6 billion annually. 2 What is worse, the cost for treating necrotizing enterocolitis clinically caused by C. perfringens in preterm infants is conservatively estimated at around £13.5 million in the UK per year. 3 Despite growing scientific concern over antibiotic resistance, a compound of penicillin combined with either clindamycin or a carbapenem is the recommended treatment of choice for this infectious disease.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For animal husbandry, necrotizing enterocolitis linked with C. perfringens is responsible for an estimated economic loss between USD$2 and $6 billion annually . What is worse, the cost for treating necrotizing enterocolitis clinically caused by C.…”
Section: Introductionmentioning
confidence: 99%